Eco-Critical Discourse Analysis in Cambodian Folktales - Sorn, Vannak; Nillawannapha, Rachan (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
This research study aims to study the Eco-Critical Discourse in Cambodian Folktales translated in Thai version, in which it was published in 1997 by the Khmer Cultural Advisory Committee. By studying document research Through information on Cambodian folktales, consisting of 8 stories, such as 1) Crocodile and cart driver 2) Animals choose to be king 3) The tradition having a sorcerer auspicious time 4) The birth of porpoise 5) The tradition of putting flowers, incense, and candles into the dead and 6) Buffalo wild and buffalo house. The result of this research found that the ecological discourse in Cambodian Folktales reflects the relationship between humans and nature and the environment. Therefore, the researcher has divided issues of the study of physical, natural image representation into three points, namely 1) Discourse Sociological meaning refers to the relation between humans and the ecosystems, family, sociology, the role of society and culture 2) Animal Discourse refers to the relationship between human and animal Cambodian folktales, and 3) Discourse Ideological meaning refers to the Environmental ideology in Cambodian folktales providing ideas that explain the relationship between humans and nature.